The Architecture of Risk and Power. A Review Article of Magnus Hornqvist, The Organised Nature of Power: On Productive and Repressive Interventions Based on Consideration of Risk, Stockholm University, 2007 - Ericson, Richard Victor (The British journal of criminology, 2007)
In The Organised Nature of Power, Magnus Hornqvist initially synthesizes Foucauldian and Marxian conceptions of power in order to highlight the connection between everyday exercises of power and power relations embedded in social structure and the state. He then proceeds to demonstrate how risk has become the coordinating mechanism in the organization of power. Risk is a common language and technology across institutions, linking exercises and structures of state power in ways that have both productive and repressive consequences. The architecture of risk and power is empirically investigated in the context of public employment, prison and customs bureaucracies in Sweden. The investigation is based on readings of policy documents, official forms, risk assessment technologies, surveillance infrastructures and case reports used in these bureaucracies. Hornqvist demonstrates how power is embedded in norms of risk management beyond the law; the multifaceted and variable uses of risk in processes of empowerment and subjection across different state bureaucracies; and the fact that we are still in disciplinary societies more than societies of control. Hornqvist's work is interrogated to indicate some limitations and directions for future research